2002
DOI: 10.1046/j.1463-1326.2002.00237.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of orlistat on body weight and glycaemic control in overweight patients with type 2 diabetes: a randomized, placebo‐controlled trial

Abstract: Treatment with orlistat plus diet resulted in significant weight loss, improved glycaemic control and cardiovascular risk factor profile in overweight patients with type 2 diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
97
1
5

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(108 citation statements)
references
References 40 publications
5
97
1
5
Order By: Relevance
“…Three were conducted in North America: two in the US alone 11,13 and one in the US and Canada. 12 The other four trials were conducted in Germany, 14 Spain, 15 Thailand 16 and South Africa. 17 The treatment duration was 1 y in four trials, [11][12][13][14] and 6 months in the other three.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three were conducted in North America: two in the US alone 11,13 and one in the US and Canada. 12 The other four trials were conducted in Germany, 14 Spain, 15 Thailand 16 and South Africa. 17 The treatment duration was 1 y in four trials, [11][12][13][14] and 6 months in the other three.…”
Section: Methodsmentioning
confidence: 99%
“…12 The other four trials were conducted in Germany, 14 Spain, 15 Thailand 16 and South Africa. 17 The treatment duration was 1 y in four trials, [11][12][13][14] and 6 months in the other three. In all protocols, patients were randomized to treatment with orlistat 120 mg or placebo t.i.d.…”
Section: Methodsmentioning
confidence: 99%
“…72 No significant effect on blood pressure compared with dietary/lifestyle-only therapy occurred, except in two studies, one of which involved subjects Long-term efficacy of weight loss methods JD Douketis et al with poorly controlled hypertension. 62,71 Orlistat had inconsistent effects on glycemic control: modest but significantly greater reductions in fasting blood glucose (0.1-1.7 mmol/l) than diet-only therapy in six studies, [60][61][62][63]67,68 but no difference in two studies. 65,66 The greatest improvements in glycemic control occurred in subjects with type 2 diabetes.…”
Section: Jd Douketis Et Almentioning
confidence: 99%
“…No study reported on weight loss and its effects of cardiovascular risk factors in high-risk groups, unless the study was limited to high-risk subjects. 67,68,70,71,73,[75][76][77] …”
Section: Jd Douketis Et Almentioning
confidence: 99%
“…Notably, obesity is often associated with a variety of chronic diseases such as hyperlipidemia, diabetes mellitus, hypertension coronary artery diseases and certain cancers ( Lei et al 2007). Thus, to reduce fat accumulation, the digestion and absorption of fat into the body should be prevented (Hanefeld and Sachse 2002). However, owing to the adverse side effects associated with many antiobesity drugs, more trials have focused on screening natural sources that have been reported to reduce body weight with minimum side effects (Rahul et al 2007).…”
Section: Introductionmentioning
confidence: 99%